The Use of Genetic Approach to the Kinematics of Cutting - Musa, Nabil Wanas (My University, 2016)
This article deals with the use of an interdisciplinary approach to modelling and creation of a complex technical system of different physical nature in relation to the kinematics of cutting and shaping. The professor of the National Technical University of Ukraine, Kuznetcov Iu. N., proposed the approach based on generalization of knowledge, methodological basis of which is the theory of evolution of the systems and methods of genetic analysis and synthesis. For generalization of the knowledge in the fundamental sciences is based on the principles of a limited number of elementary generic structures with the introduction of the gene concept. The modelling and synthesis of kinematic cutting schemes are providing the efficiency and viability of genetic and morphological approach. The material point, which can interact with other material points in space and time, simulating anthropogenic system of different origin, is introduced as a material object
Keywords: Genetic Approach; Kinematics of Cutting; Technical System; Rotary Motion; Material Point